Membrane electrode, method for producing the same, and use thereof

CN116826098BActive Publication Date: 2026-10-30FAW JIEFANG AUTOMOTIVE CO
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310735381.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-20
Publication Date
2026-10-30
Estimated Expiration
2043-06-20

AI Technical Summary

Technical Problem

膜电极双边框密封结构中,边框分为阴、阳两层,将质子交换膜或CCM密封在阴、阳两层边框中,边框胶层覆盖所有边框区域,具有边框胶层的使用量大、成本浪费的缺点

Benefits of technology

[0038]本申请提供的膜电极,具有依次密封住第一密封层、质子膜层和第一气体扩散层的端面的第一密封屏障,并配合依次密封住所述第二密封层、所述质子膜层和所述第二气体扩散层的端面的第二密封屏障,在第一密封屏障和第二密封屏障的相互配合下,能够有效提供高结合力,能够进一步保障膜电极的气密性,以提高膜电极的耐久性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116826098B_ABST
    Figure CN116826098B_ABST
Patent Text Reader

Abstract

The membrane electrode provided by the application has a first sealing barrier for sealing the end face of the first sealing layer, the proton membrane layer and the first gas diffusion layer in sequence, and cooperates with a second sealing barrier for sealing the end face of the second sealing layer, the proton membrane layer and the second gas diffusion layer in sequence, so that high bonding force can be effectively provided under the cooperation of the first sealing barrier and the second sealing barrier, and the air tightness of the membrane electrode can be further ensured to improve the durability of the membrane electrode. Further, the membrane electrode provided by the application has the sealing layer arranged on the end face of the gas diffusion layer, so that the contact area of the sealing layer and the gas diffusion layer can be reduced while the gas diffusion layer is fixed, and the active area of the membrane electrode is ensured, so as to further improve the volume power density of the stack.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of fuel cell technology, specifically to a membrane electrode, its preparation method, and its application. Background Technology

[0002] A proton exchange membrane fuel cell (PEMFC) is a device that uses the electrochemical reaction between hydrogen and oxygen to convert chemical energy into electrical energy. PEMFCs have advantages such as low operating temperature and fast start-up speed, and have a very broad application prospect in new energy vehicles.

[0003] The core components of a PEMFC mainly include the membrane electrode assembly (MEA) and bipolar plates. The MEA is composed of a proton exchange membrane (PEM), a catalyst layer, a frame, and a gas diffusion layer. The MEA frame is a polymer framework that seals the MEA, primarily providing mechanical support, separating fuel from air in the anode and cathode spaces, providing electrical insulation, and providing a sealing surface for the cell unit. Currently, MEA sealing structures mainly include double-frame and single-frame structures. In a double-frame MEA structure, the frame consists of anode and cathode layers, sealing the PEM or CCM within these two layers. The adhesive layer covers the entire frame area, resulting in a large amount of adhesive used and wasted cost. In a single-frame MEA structure, the PEM or CCM is fixed to the frame on only one side, and the sealing stress on both sides of the PEM or CCM is asymmetrical, leading to reduced durability of the MEA frame seal. Summary of the Invention

[0004] Based on this, this application provides a membrane electrode, its preparation method, and its application. The membrane electrode provided by this application can reduce the use of membrane electrode sealing materials and has excellent sealing durability.

[0005] A first aspect of this application provides a membrane electrode, comprising a proton exchange membrane layer, a first gas diffusion layer, a second gas diffusion layer, a first sealing layer, a second sealing layer, a first frame, and a second frame.

[0006] The proton exchange membrane layer includes a first surface and a second surface disposed opposite to each other;

[0007] The first gas diffusion layer is disposed on the first surface, and the second gas diffusion layer is disposed on the second surface;

[0008] A first sealing layer is disposed on the first surface and connected to the first gas diffusion layer; and the first sealing layer extends out of the first surface in a direction away from the first gas diffusion layer; wherein the thickness of the first sealing layer is ≥10μm, and the overlap length between the first sealing layer and the first surface is ≥2mm;

[0009] A first frame is disposed on the side of the first sealing layer opposite to the first surface to provide support for the first sealing layer;

[0010] The second sealing layer includes a first sealing portion, a second sealing portion, and an intermediate portion. The first sealing portion is embedded in the end of the first sealing layer away from the first gas diffusion layer. The second sealing portion is disposed on the second surface and is connected to the second gas diffusion layer. The end of the second sealing portion away from the second gas diffusion layer extends obliquely towards the first sealing portion to form the intermediate portion. The thickness of the second sealing layer is ≥10μm, and the overlap length between the second sealing layer and the second surface is ≥3mm.

[0011] A second frame is disposed on the side of the second sealing layer opposite to the second surface, and is used to provide support for the second sealing layer; the shape of the second frame is adapted to the shape of the second sealing layer.

[0012] In one embodiment, a gap is left between the end face of the first frame near the first gas diffusion layer and the first gas diffusion layer, and the gap is filled by the first sealing layer;

[0013] And / or, the second frame includes a first support portion, a second support portion, and a middle support portion. The first support portion is disposed on the side of the first sealing portion away from the first sealing layer, and the second support portion is disposed on the side of the second sealing portion away from the second surface. A gap is left between the end face of the second support portion near the second gas diffusion layer and the second gas diffusion layer, and the gap is filled by the second sealing portion. The end of the second support portion away from the second gas diffusion layer extends obliquely towards the first support portion to form a middle support portion, and the middle support portion is disposed on the side of the middle portion away from the proton membrane layer.

[0014] In one embodiment, the first sealing layer is formed by curing a first hot melt adhesive, the glass transition temperature of which is 80°C to 100°C.

[0015] And / or, the second sealing layer is formed by curing a second hot melt adhesive; the glass transition temperature of the second hot melt adhesive is 80°C to 100°C.

[0016] In one embodiment, the membrane electrode has one or more of the following features:

[0017] (1) The material of the first hot melt adhesive forming the first sealing layer is a protophilic membrane polymer;

[0018] (2) The material of the second hot melt adhesive forming the second sealing layer is a first border-affinity polymer and / or a second border-affinity polymer;

[0019] (3) The thickness of the first sealing layer is 10μm to 50μm;

[0020] (4) The thickness of the second sealing layer is 10μm to 50μm.

[0021] In one embodiment, the overlap length between the first sealing layer and the first surface is 2mm to 4mm, and the peel strength between the first sealing layer and the first surface is ≥5N / cm.

[0022] The overlap length between the second sealing layer and the second surface is 3mm to 6mm, and the peel strength between the second sealing layer and the second surface is ≥5N / cm;

[0023] The length of the first sealing part embedded in the first sealing layer is 1mm to 1.6mm, and the peel strength between the first sealing part and the first sealing layer is ≥7N / cm.

[0024] In one embodiment, the gap length between the end face of the first frame near the first gas diffusion layer and the first gas diffusion layer is 0.3mm to 0.5mm; the gap length between the end face of the second support near the second gas diffusion layer and the second gas diffusion layer is 0.3mm to 0.5mm; the first sealing portion overflows from the end of the first support portion away from the proton membrane layer, and the overflow length of the first sealing portion is 0.3mm to 0.5mm.

[0025] In one embodiment, the proton membrane layer includes a proton exchange membrane and catalytic layers disposed on two opposite surfaces of the proton exchange membrane, wherein the outer dimensions of the catalytic layers are 0 mm to 2.7 mm smaller than the outer dimensions of the proton exchange membrane.

[0026] In one embodiment, the membrane electrode has one or more of the following features:

[0027] (1) The thickness of the proton membrane is 20 μm to 50 μm;

[0028] (2) The thickness of the first gas diffusion layer and / or the second gas diffusion layer is 150 μm to 300 μm;

[0029] (3) The thickness of the first border and / or the second border is 12.5μm to 200μm;

[0030] (4) The material of the first frame and / or the second frame includes one or more of polyethylene terephthalate, polyimide, polyethylene naphthalate, polyphenylene sulfide and polyetheretherketone.

[0031] In one embodiment, the membrane electrode further includes a first electrode stack sealing strip and a second electrode stack sealing strip, which are respectively disposed on two opposite surfaces of the first frame and at one end of the first frame away from the first gas diffusion layer.

[0032] In one embodiment, the materials of the first and second fuel cell stack sealing strips are independently selected from one or more of silicone rubber, EPDM rubber, polyolefin rubber, fluororubber, polyurethane rubber, and polyetheretherketone rubber.

[0033] A second aspect of this application provides a method for preparing a membrane electrode according to any embodiment of the first aspect of this application, comprising the following steps:

[0034] The first gas diffusion layer and the second gas diffusion layer are respectively placed on two opposite surfaces of the proton membrane layer;

[0035] The first frame coated with a first hot melt adhesive and the second frame coated with a second hot melt adhesive are placed and hot-pressed together, and the first hot melt adhesive and / or the second hot melt adhesive are cured to form the first sealing layer and the second sealing layer, thereby preparing the membrane electrode.

[0036] In one embodiment, the hot pressing process parameters include: a hot pressing pressure of 1 kg / cm². 2 ~20kg / cm 2 The hot pressing temperature is 80℃~150℃.

[0037] A third aspect of this application provides a proton exchange membrane fuel cell, comprising a membrane electrode as described in any embodiment of the first aspect of this application and a membrane electrode prepared by the preparation method described in any embodiment of the second aspect of this application.

[0038] The membrane electrode provided in this application has a first sealing barrier that sequentially seals the end faces of a first sealing layer, a proton membrane layer, and a first gas diffusion layer, and a second sealing barrier that sequentially seals the end faces of a second sealing layer, the proton membrane layer, and the second gas diffusion layer. With the cooperation of the first sealing barrier and the second sealing barrier, high bonding force can be effectively provided, which can further ensure the airtightness of the membrane electrode and improve the durability of the membrane electrode.

[0039] Furthermore, in the second sealing layer, the intermediate layer connects the first sealing part and the second sealing part, improving the airtightness of the second sealing layer; at the same time, with the cooperation of the first sealing layer, there is no structural height difference in the coverage area of ​​the gas diffusion layer, eliminating the electrochemical corrosion caused by the air triangle region, as well as the phenomenon that the gas diffusion layer is affected by overpressure due to height difference.

[0040] Furthermore, the membrane electrode provided in this application has a sealing layer disposed on the end face of the gas diffusion layer, which can reduce the contact area between the sealing layer and the gas diffusion layer while fixing the gas diffusion layer, thereby ensuring the active area of ​​the membrane electrode and further improving the volumetric power density of the fuel cell stack. Attached Figure Description

[0041] Figure 1 This is a schematic diagram of the membrane electrode structure of this application;

[0042] Figure 2 This is a schematic diagram of the structure of the second border of this application.

[0043] Explanation of reference numerals in the attached figures:

[0044] 10. Membrane electrode; 11. Proton exchange membrane layer; 111. First surface; 112. Second surface; 12. First gas diffusion layer; 13. Second gas diffusion layer; 14. First sealing layer; 15. First frame; 16. Second sealing layer; 161. First sealing part; 162. Second sealing part; 163. Middle part; 17. Second frame; 171. First support part; 172. Second support part; 173. Middle support part; 18. First fuel cell stack sealing strip; 19. Second fuel cell stack sealing strip. Detailed Implementation

[0045] The membrane electrode 10 of this application, its preparation method, and its application are further described in detail below with reference to specific embodiments. This application can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of this application.

[0046] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein in the specification of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.

[0047] In this article, "one or more" refers to any one, two or more of the listed items.

[0048] In this application, terms such as "first," "second," "third," "fourth," and "fifth" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. Moreover, terms such as "first," "second," "third," "fourth," and "fifth" serve only as a non-exhaustive enumeration and should be understood not to constitute a closed limitation on quantity.

[0049] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.

[0050] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values ​​of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.

[0051] Unless otherwise specified, the percentage content mentioned in this application refers to mass percentage for solid-liquid mixtures and solid-phase-solid mixtures, and volume percentage for liquid-phase-liquid mixtures.

[0052] Unless otherwise specified, all percentage concentrations mentioned in this application refer to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of that component.

[0053] Unless otherwise specified, the temperature parameters in this application may be either constant temperature processing or processing within a certain temperature range. The constant temperature processing allows for temperature fluctuations within the precision range controlled by the instrument.

[0054] Please see Figure 1 In a first aspect, this application provides a membrane electrode 10, comprising a proton membrane layer 11, a first gas diffusion layer 12, a second gas diffusion layer 13, a first sealing layer 14, a first frame 15, a second sealing layer 16, and a second frame 17.

[0055] The proton exchange membrane layer 11 includes a first surface 111 and a second surface 112 disposed opposite to each other;

[0056] A first gas diffusion layer 12 is disposed on a first surface 111, and a second gas diffusion layer 13 is disposed on a second surface 112;

[0057] The first sealing layer 14 is disposed on the first surface 111 and connected to the first gas diffusion layer 12; and the first sealing layer 14 extends from the first surface 111 in a direction away from the first gas diffusion layer 12; wherein the thickness of the first sealing layer 14 is ≥10μm, and the overlap length between the first sealing layer 14 and the first surface 111 is ≥2mm.

[0058] The first frame 15 is disposed on the side of the first sealing layer 14 opposite to the first surface 111 to provide support for the first sealing layer 14;

[0059] The second sealing layer 16 includes a first sealing portion 161, a second sealing portion 162, and an intermediate portion 163. The first sealing portion 161 is embedded in the end of the first sealing layer 14 away from the first gas diffusion layer 12. The second sealing portion 162 is disposed on the second surface 112 and is connected to the second gas diffusion layer 13. The end of the second sealing portion 162 away from the second gas diffusion layer 13 extends obliquely toward the first sealing portion 161 to form the intermediate portion 163. The thickness of the second sealing layer 16 is ≥10μm, and the overlap length between the second sealing layer 16 and the second surface 112 is ≥3mm.

[0060] The second frame 17 is disposed on the side of the second sealing layer 16 away from the second surface 112, and is used to provide support for the second sealing layer 16; the shape of the second frame 17 is adapted to the shape of the second sealing layer 16.

[0061] The membrane electrode 10 provided in this application has a first sealing barrier that sequentially seals the end faces of the first sealing layer 14, the proton membrane layer 11 and the first gas diffusion layer 12, and a second sealing barrier that sequentially seals the end faces of the second sealing layer 16, the proton membrane layer 11 and the second gas diffusion layer 13. With the cooperation of the first sealing barrier and the second sealing barrier, high bonding force can be effectively provided, which can further ensure the airtightness of the membrane electrode 10 and improve the durability of the membrane electrode 10.

[0062] Furthermore, in the second sealing layer 16, the intermediate layer can connect the first sealing part 161 and the second sealing part 162, thereby improving the airtightness of the second sealing layer. At the same time, with the cooperation of the first sealing layer 14, the coverage area of ​​the gas diffusion layer is free from structural height differences, eliminating the electrochemical corrosion of the proton membrane layer caused by the air triangle region, as well as the phenomenon that the gas diffusion layer is affected by overpressure due to height differences, thus affecting gas transmission.

[0063] Furthermore, the membrane electrode 10 provided in this application has a sealing layer disposed on the end face of the gas diffusion layer, which can reduce the contact area between the sealing layer and the gas diffusion layer while fixing the gas diffusion layer, thereby ensuring the active area of ​​the membrane electrode 10 and further improving the volumetric power density of the stack.

[0064] In one example, a gap is left between the end face of the first frame 15 near the first gas diffusion layer 12 and the first gas diffusion layer 12. The gap is filled by the first sealing layer 14. The gap is used to accommodate the assembly tolerance of the gas diffusion layer, prevent the gas diffusion layer from overlapping with the frame, causing electrochemical corrosion of the proton membrane due to the air triangle region, and prevent the gas diffusion layer from being affected by overpressure due to the height difference.

[0065] In one example, the second frame 17 includes a first support portion 171, a second support portion 172, and a middle support portion 173. The first support portion 171 is disposed on the side of the first sealing portion 161 away from the first sealing layer 14. The second support portion 172 is disposed on the side of the second sealing portion 162 away from the second surface 112. A gap is left between the end face of the second support portion 172 near the second gas diffusion layer 13 and the second gas diffusion layer 13. The gap is filled by the second sealing portion 162. The gap is used to accommodate the assembly tolerance of the gas diffusion layer, preventing the gas diffusion layer from overlapping with the frame and causing electrochemical corrosion of the proton membrane due to the air triangle region, as well as the phenomenon that the gas diffusion layer affects gas transmission due to overpressure caused by the height difference. The end of the second support portion 172 away from the second gas diffusion layer 13 extends obliquely towards the first support portion 171 to form the middle support portion 173. The middle support portion 173 is disposed on the side of the middle portion 163 away from the proton membrane layer 11.

[0066] In one example, the first sealing layer 14 is formed by curing a first hot melt adhesive, the first hot melt adhesive having a glass transition temperature of 80°C to 100°C. It is understood that the glass transition temperature of the first hot melt adhesive can be selected from any value between 80°C and 100°C. Specifically, the glass transition temperature includes, but is not limited to, 80°C, 81°C, 82°C, 85°C, 87°C, 88°C, 89°C, or 90°C.

[0067] In one example, the second sealing layer 16 is formed by curing a second hot melt adhesive; the glass transition temperature of the second hot melt adhesive is 80°C to 100°C. It is understood that the glass transition temperature of the second hot melt adhesive can be selected from any value within the range of 80°C to 100°C. Specifically, the glass transition temperature includes, but is not limited to, 80°C, 81°C, 82°C, 85°C, 87°C, 88°C, 89°C, or 90°C. Selecting a hot melt adhesive within this glass transition temperature range allows the glass transition temperature to be higher than the operating temperature, preventing frequent phase changes within the operating temperature range from affecting the durability of the hot melt adhesive and influencing the mechanical performance design.

[0068] In one example, the material of the first hot melt adhesive forming the first sealing layer 14 is a proton-loving membrane polymer. By selecting a proton-loving membrane polymer, the peel strength between the first sealing layer 14 and the proton membrane layer 11 can be guaranteed.

[0069] In one example, the material of the second hot melt adhesive forming the second sealing layer 16 is a first-border-affinity polymer and / or a second-border-affinity polymer. The second hot melt adhesive is selected from sealants that are different from the first hot melt adhesive and are affinity-affinity ...

[0070] Furthermore, the overlap length between the first sealing layer 14 and the first surface 111 is 2mm to 4mm, and the peel strength between the first sealing layer 14 and the first surface 111 is ≥5N / cm. In this application, "overlap length" refers to the horizontal distance between the two surfaces. Within this range, the overlap length ensures that the first sealing layer 14 is completely filled to prevent leakage, and also guarantees the peel strength between the first sealing layer 14 and the first surface 111. When the peel strength is ≥5N / cm, the internal stress generated by the periodic changes in temperature and humidity in the proton exchange membrane layer 11 can be effectively avoided, thereby effectively ensuring the airtightness of the membrane electrode 10.

[0071] Meanwhile, the first sealing portion 161 attached to the surface of the first support portion 171 in the second frame 17 adheres to the first sealing layer 14 attached to the surface of the first frame 15, which can further increase the peel strength between the first sealing portion 161 and the second sealing layer 16. Further, the length of the first sealing portion 161 embedded in the first sealing layer 14 is 1mm to 1.6mm, and the peel strength between the first sealing portion 161 and the first sealing layer 14 is ≥7N / cm. When the peel strength between the first sealing portion 161 and the first sealing layer 14 is ≥7N / cm, the airtightness between the second sealing layer 16 and the first sealing layer 14 can be guaranteed. When the peel strength is low, the airtightness durability between the second sealing layer 16 and the first sealing layer 14 is slightly weaker, thus making the airtightness durability of the membrane electrode 10 slightly weaker. In one example, the overlap length between the second sealing layer 16 and the second surface 112 is 3mm to 6mm, and the peel strength between the second sealing layer 16 and the second surface 112 is ≥5N / cm.

[0072] In one example, the thickness of the first sealing layer 14 and / or the second sealing layer 16 is 10 μm to 50 μm. The thickness of the first sealing layer 14 and the second sealing layer 16 can be independently selected from any value between 10 μm and 50 μm. Specifically, the thickness of the first sealing layer 14 and / or the second sealing layer 16 includes, but is not limited to, 10 μm, 20 μm, 30 μm, 40 μm, or 50 μm. The first sealing layer 14 and / or the second sealing layer 16 selected within this thickness range have excellent sealing performance and can prevent increased costs and impact on the performance of the assembled electrode stack when the thickness is large; at the same time, it can prevent the peel strength and sealing durability of the membrane electrode 10 from being slightly weak when the thickness of the first sealing layer 14 and / or the second sealing layer 16 is small.

[0073] In one example, the overlap length between the first surface 111 and the first border 15 is 1.5mm to 3.7mm, and the overlap length between the second surface 112 and the second border 17 is 2.5mm to 5.7mm. Specifically, the overlap length between the first surface 111 and the first border 15 includes, but is not limited to, 1.5mm, 1.8mm, 2mm, 2.5mm, 2.8mm, 3mm, 3.2mm, 3.5mm, or 3.7mm. The overlap length between the second surface 112 and the second border 17 includes, but is not limited to, 2.5mm, 2.8mm, 3mm, 3.5mm, 4mm, 4.5mm, 5mm, 5.3mm, 5.5mm, or 5.7mm.

[0074] In one example, the gap length between the end face of the first frame 15 near the first gas diffusion layer 12 and the first gas diffusion layer 12 is 0.3mm to 0.5mm; the gap length between the end face of the second support 172 near the second gas diffusion layer 13 and the second gas diffusion layer 13 is 0.3mm to 0.5mm. Setting the gap lengths between the first frame 15 and the first gas diffusion layer 12, and between the second frame 172 and the second gas diffusion layer 13, to 0.3mm to 0.5mm satisfies the assembly tolerances of the membrane electrode 10 and prevents the two materials from overlapping. If the gaps are large, the effective area of ​​the membrane electrode 10 is small, resulting in a lower volumetric power density of the fuel cell stack.

[0075] Understandable, such as Figure 1 As shown, the first sealing portion 161 extends beyond the end of the first support portion 171 away from the proton exchange membrane layer 11, with an overflow length of 0.3mm to 0.5mm. This further ensures that the first sealing layer 14 and the second sealing layer 16 are fully bonded. Specifically, the overflow length of the first sealing portion includes, but is not limited to, 0.3mm, 0.4mm, or 0.5mm. The overflow of the first sealing portion can effectively prevent the airtightness of the first frame 15 and the second frame 17 from failing.

[0076] In one example, the proton exchange membrane layer 11 includes a proton exchange membrane and catalyst layers respectively disposed on two opposite surfaces of the proton exchange membrane. The outer dimensions of the catalyst layers are 0 mm to 2.7 mm smaller than the outer dimensions of the proton exchange membrane. Preferably, the proton exchange membrane is a perfluorosulfonic acid resin proton exchange membrane. The catalyst layers can promote the catalytic action of hydrogen and oxygen in the electrochemical reaction, accelerate the transfer between electrons and ions, and thus improve the efficiency and performance of the fuel cell. The fact that the outer dimensions of the catalyst layers are 0 mm to 2.7 mm smaller than the outer dimensions of the proton exchange membrane improves the adhesion between the proton exchange membrane and the frame, while reducing the cost of the catalyst layers. It is understood that "outer dimensions" here refers to the requirement that the length and / or width of the catalyst layers be 0 mm to 2.7 mm smaller than the length and / or width of the proton exchange membrane.

[0077] In one example, the thickness of the proton exchange membrane 11 is 20 μm to 50 μm. Specifically, the thickness of the proton exchange membrane 11 includes, but is not limited to, 20 μm, 30 μm, 40 μm, 45 μm, or 50 μm.

[0078] In one example, the thickness of the first gas diffusion layer 12 and / or the second gas diffusion layer 13 is 150 μm to 300 μm. Specifically, the thickness of the first gas diffusion layer 12 and / or the second gas diffusion layer 13 includes, but is not limited to, 150 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 250 μm, 280 μm, 290 μm, or 300 μm.

[0079] In one example, the thickness of the first border 15 and / or the second border 17 is 12.5 μm to 200 μm. Specifically, the thickness of the first border 15 and / or the second border 17 can be 12.5 μm, 30 μm, 50 μm, 75 μm, 100 μm, 150 μm, or 200 μm, but is not limited to the listed values; other unlisted values ​​within the range are also applicable. This is to prevent the border from being too thin, which would result in slightly lower border durability.

[0080] In one example, the material of the first border 15 and / or the second border 17 includes one or more of polyethylene terephthalate, polyimide, polyethylene naphthalate, polyphenylene sulfide, and polyetheretherketone.

[0081] The fuel cell stack sealing strip prevents leakage of substances such as hydrogen, oxygen, and moisture from the fuel cell system. In one example, the membrane electrode 10 also includes a first stack sealing strip 18 and a second stack sealing strip 19, which are respectively disposed on two opposite surfaces of the first frame 15, and at the end of the first frame 15 away from the proton exchange membrane layer 11. The stack sealing strips, disposed on the first frame 15 of the membrane electrode 10, avoid problems such as stress concentration caused by stack assembly deviations leading to misalignment of the cathode / anode sealing strips, and height differences between stack plates affecting performance consistency.

[0082] Understandably, in order to assemble the first fuel cell stack sealing strip 18 and the second fuel cell stack sealing strip 19 on the first frame 15, the horizontal length of the first frame 15 needs to be greater than the horizontal length of the second frame 17.

[0083] Preferably, the thickness of the first fuel cell stack sealing strip 18 is 500 μm to 930 μm. For example, it can be 500 μm, 600 μm, 700 μm, 800 μm or 930 μm, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0084] The thickness of the second fuel cell stack sealing strip 19 is 670μm to 1200μm. For example, it can be 670μm, 800μm, 900μm, 1000μm, 1100μm or 1200μm, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0085] Furthermore, the gap between the second fuel cell stack sealing strip 19 and the second sealing layer 16 is 0.3mm to 0.5mm. For example, it can be 0.3mm, 0.4mm or 0.5mm, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0086] In one example, the materials of the first fuel cell stack sealing strip 18 and the second fuel cell stack sealing strip 19 are independently selected from one or more of silicone rubber, EPDM rubber, polyolefin rubber, fluororubber, polyurethane rubber and polyetheretherketone rubber.

[0087] A second aspect of this application provides a method for preparing the membrane electrode 10 described in any example of the first aspect of this application, comprising the following steps:

[0088] The first gas diffusion layer 12 and the second gas diffusion layer 13 are respectively placed on two opposite surfaces of the proton membrane layer 11;

[0089] A first frame 15 coated with a first hot melt adhesive and a second frame 17 coated with a second hot melt adhesive are placed and hot-pressed, and the first hot melt adhesive and / or the second hot melt adhesive are cured to form a first sealing layer 14 and / or a second sealing layer 16, thereby preparing a membrane electrode 10.

[0090] In one example, the hot pressing process parameters include: a hot pressing pressure of 1 kg / cm². 2 ~20kg / cm 2 The hot pressing temperature is 80℃~150℃.

[0091] In one example, the hot pressing process parameters include a hot pressing time of 10 seconds to 5 minutes.

[0092] In one example, the method of applying the first hot melt adhesive and the second hot melt adhesive includes one or more of screen printing, squeegeeing, spraying, or brushing.

[0093] In one example, the hot-pressing position is the entire second border, and the outer dimensions of the hot-pressing mold are 0.3mm to 0.5mm longer than the second border. Understandably, "outer dimensions" here refers to the fact that the length and / or width of the hot-pressing mold needs to be 0.3mm to 0.5mm longer than the length and / or width of the second border.

[0094] Specifically, the preparation method of the membrane electrode 10 includes the following steps:

[0095] S1. Select a proton membrane layer 11, and set a second gas diffusion layer 13 on the second surface 112 of the proton membrane layer 11. Set a first gas diffusion layer 12 on the first surface 111 of the proton membrane layer 11. The first gas diffusion layer 12 and the second gas diffusion layer are disposed opposite to each other on the two surfaces of the proton membrane layer 11.

[0096] S2. Select a first frame 15 with a first fuel cell stack sealing strip 18 on the upper surface and a second fuel cell stack sealing strip 19 on the lower surface. Apply the first hot melt adhesive to the surface of the first frame 15 and place the first frame 15 on the first surface 111 of the proton membrane layer 11, leaving a gap between the first frame 15 and the first gas diffusion layer 12.

[0097] S3. Apply the second hot melt adhesive to the surface of the second frame 17, place the second frame 17, and leave a gap between the second support 172 and the second gas diffusion layer 13.

[0098] S4. Hot-press the second frame 17 in a molding press, covering the entire second frame 17. The outer dimensions of the hot-pressing mold are 0.3mm to 0.5mm longer than the second frame, and the molding pressure is 1kg / cm². 2 ~20kg / cm 2The hot-pressing temperature is 80℃~150℃, and the hot-pressing time is 10s~5min; the first hot melt adhesive and the second hot melt adhesive form the first sealing layer 14 and the second sealing layer 16, and the thickness of the first sealing layer 14 and the second sealing layer 16 is 10μm~50μm; at the same time, the second hot melt adhesive overflows from the end of the first support portion 171 in the second frame 17 away from the proton membrane layer 11, and the second hot melt adhesive adheres to the upper surface of the first frame 15. The overlap length between the overflowing second hot melt adhesive and the first frame 15 is 0.3mm~0.5mm, thus preparing the membrane electrode 10.

[0099] More specifically, the method for preparing the membrane electrode 10 includes the following steps:

[0100] S10. Select a proton membrane layer 11 with a thickness of 20μm to 50μm, and set a second gas diffusion layer 13 with a thickness of 150μm to 300μm on the upper surface of the proton membrane layer 11. Set a first gas diffusion layer 12 with a thickness of 150μm to 300μm on the lower surface of the proton membrane layer 11. The first gas diffusion layer 12 and the second gas diffusion layer 13 are disposed opposite to each other on the two surfaces of the proton membrane layer 11.

[0101] S20. Select a first frame 15 (thickness 12.5μm~200μm) with a first fuel cell stack sealing strip 18 injection-molded on the upper surface and a second fuel cell stack sealing strip 19 injection-molded on the lower surface. Apply the first hot melt adhesive to the surface of the first frame 15 and place the first frame 15 such that the overlap length between the first frame 15 and the proton exchange membrane layer 11 is 1.5mm~3.7mm, and the gap between the first frame 15 and the first gas diffusion layer 12 is 0.3mm~0.5mm.

[0102] S30. Apply the second hot melt adhesive to the surface of the second frame 17 (thickness 12.5μm~200μm), place the second frame 17 such that the overlap length between the second frame 17 and the proton exchange membrane layer 11 is 2.5mm~5.7mm, and the gap between the second frame 17 and the second gas diffusion layer 13 is 0.3mm~0.5mm.

[0103] S40. Hot-press the second frame 17 in a molding press, covering the entire second frame 17. The outer dimensions of the hot-pressing mold are 0.3mm to 0.5mm longer than the second frame, and the molding pressure is 1kg / cm². 2 ~20kg / cm 2The hot-pressing temperature is 80℃~150℃, and the hot-pressing time is 10s~5min. The thickness of the first hot melt adhesive and the second hot melt adhesive is 10μm~50μm. The overlap length between the first hot melt adhesive and the proton exchange membrane layer 11 is 2mm~4mm, and the peel strength between the first hot melt adhesive and the proton exchange membrane layer 11 is ≥5N / cm. At the same time, the overlap length between the first hot melt adhesive and the second hot melt adhesive is 1mm~1.6mm, and the peel strength between the first hot melt adhesive and the second hot melt adhesive is ≥7N / cm. The overlap length between the second hot melt adhesive and the proton exchange membrane layer 11 is 3mm~6mm, and the peel strength between the first hot melt adhesive and the proton exchange membrane layer 11 is ≥5N / cm. Meanwhile, the second hot melt adhesive overflows from the end of the second frame 17 away from the proton exchange membrane layer 11 and adheres to the upper surface of the first frame 15. The overlap length between the overflowing second hot melt adhesive and the first frame 15 is 0.3mm~0.5mm, thus preparing the membrane electrode 10.

[0104] A third aspect of this application provides a proton exchange membrane fuel cell, including the membrane electrode 10 described in any example of the first aspect of this application and the membrane electrode prepared by the preparation method described in the second aspect of this application.

[0105] The following are specific examples. Unless otherwise specified, the raw materials used in the examples are all commercially available products.

[0106] Example 1

[0107] Embodiment 1 of this application provides a membrane electrode 10, including a proton exchange membrane layer 11 with a thickness of 50 μm, a second gas diffusion layer 13 with a thickness of 300 μm disposed on the upper surface of the proton exchange membrane layer 11, and a first gas diffusion layer 12 with a thickness of 300 μm disposed on the lower surface of the proton exchange membrane layer 11. The first gas diffusion layer 12 and the second gas diffusion layer 13 are disposed opposite to each other on the two surfaces of the proton exchange membrane layer 11. A first frame 15 (thickness of 200 μm and horizontal length of 11 mm) is selected, with a first electrode stack sealing strip 18 (thickness of 500 μm) injection molded on the upper surface and a second electrode stack sealing strip 19 (thickness of 670 μm) injection molded on the lower surface. A first hot melt adhesive (proton exchange membrane polymer, glass transition temperature 100°C) is applied to the surface of the first frame 15. The first frame 15 is placed such that the overlap length between the first frame 15 and the proton exchange membrane layer 11 is 3.5 mm, and the gap between the first frame 15 and the first gas diffusion layer 12 is 0.5 mm.

[0108] A second hot melt adhesive (border-affinity polymer, glass transition temperature 100°C) is applied to the surface of the second border 17 (200 μm thick, 8 mm horizontal length). The second border 17 is then positioned such that the overlap length between the second border 17 and the proton exchange membrane layer 11 is 5.5 mm, and the gap between the second border 17 and the second gas diffusion layer 13 is 0.5 mm.

[0109] The second frame 17 is molded in a molding machine at a molding pressure of 20 kg / cm². 2 The hot-pressing temperature is 150℃, and the hot-pressing time is 10s. The thickness of the first hot melt adhesive and the second hot melt adhesive is 50μm. The overlap length between the first hot melt adhesive and the proton exchange membrane layer 11 is 4mm, and the peel strength between the first hot melt adhesive and the proton exchange membrane layer 11 is 6N / cm. The overlap length between the second hot melt adhesive and the proton exchange membrane layer 11 is 6mm, and the peel strength between the first hot melt adhesive and the proton exchange membrane layer 11 is 6N / cm. At the same time, the overlap length between the first hot melt adhesive and the second hot melt adhesive is 1.6mm, and the peel strength between the first hot melt adhesive and the second hot melt adhesive is 8N / cm. Simultaneously, the second hot melt adhesive overflows from the end of the second frame 17 away from the proton exchange membrane layer 11 and adheres to the upper surface of the first frame 15. The overlap length between the overflowing second hot melt adhesive and the first frame 15 is 0.5mm, thus preparing the membrane electrode 10.

[0110] Example 2

[0111] A proton membrane layer 11 with a thickness of 20 μm is selected. A second gas diffusion layer 13 with a thickness of 150 μm is disposed on the upper surface of the proton membrane layer 11, and a first gas diffusion layer 12 with a thickness of 150 μm is disposed on the lower surface of the proton membrane layer 11. The first gas diffusion layer 12 and the second gas diffusion layer 13 are disposed opposite to each other on the two surfaces of the proton membrane layer 11.

[0112] A first frame 15 (12.5 μm thick) with a first fuel cell stack sealing strip 18 (930 μm thick) molded on its upper surface and a second fuel cell stack sealing strip 19 (1200 μm thick) molded on its lower surface was selected. A first hot melt adhesive (proton-loving membrane polymer, glass transition temperature 80°C) was applied to the surface of the first frame 15. The first frame 15 was then placed such that the overlap length between the first frame 15 and the proton cell membrane 11 was 1.7 mm, and the gap between the first frame 15 and the first gas diffusion layer 12 was 0.3 mm.

[0113] A second hot melt adhesive (border-affinity polymer, glass transition temperature 80°C) is applied to the surface of the second border 17 (12.5 μm thick). The second border 17 is then placed such that the overlap length between the second border 17 and the proton exchange membrane layer 11 is 2.7 mm, and the gap between the second border 17 and the second gas diffusion layer 13 is 0.3 mm.

[0114] The second frame 17 is molded in a molding machine at a molding pressure of 1 kg / cm². 2The hot-pressing temperature is 80℃, and the hot-pressing time is 5 minutes. The thickness of the first hot melt adhesive and the second hot melt adhesive is 10 μm. The overlap length between the first hot melt adhesive and the proton exchange membrane layer 11 is 2 mm, and the peel strength between the first hot melt adhesive and the proton exchange membrane layer 11 is 5 N / cm. The overlap length between the second hot melt adhesive and the proton exchange membrane layer 11 is 3 mm. The peel strength between the first hot melt adhesive and the proton exchange membrane layer 11 is 5 N / cm. The overlap length between the first hot melt adhesive and the second hot melt adhesive is 1 mm, and the peel strength between the first hot melt adhesive and the second hot melt adhesive is 7 N / cm. At the same time, the second hot melt adhesive overflows from the end of the second frame 17 away from the proton exchange membrane layer 11 and adheres to the upper surface of the first frame 15. The overlap length between the overflowing second hot melt adhesive and the first frame 15 is 0.3 mm, thus preparing the membrane electrode 10.

[0115] Example 3

[0116] A proton membrane layer 11 with a thickness of 30 μm is selected. A second gas diffusion layer 13 with a thickness of 200 μm is disposed on the upper surface of the proton membrane layer 11, and a first gas diffusion layer 12 with a thickness of 200 μm is disposed on the lower surface of the proton membrane layer 11. The first gas diffusion layer 12 and the second gas diffusion layer 13 are disposed opposite to each other on the two surfaces of the proton membrane layer 11.

[0117] A first frame 15 (100μm thick) with a first fuel cell stack sealing strip 18 (800μm thick) molded on its upper surface and a second fuel cell stack sealing strip 19 (800μm thick) molded on its lower surface is selected. A first hot melt adhesive (proton-loving membrane polymer, glass transition temperature 100℃) is applied to the surface of the first frame 15. The first frame 15 is then placed such that the overlap length between the first frame 15 and the proton cell membrane 11 is 2.5mm, and the gap between the first frame 15 and the first gas diffusion layer 12 is 0.4mm.

[0118] S30. Apply a second hot melt adhesive (border-affinity polymer, glass transition temperature 80°C) to the surface of the second border 17 (100 μm thick), and place the second border 17 such that the overlap length between the second border 17 and the proton exchange membrane layer 11 is 4.5 mm, and the gap between the second border 17 and the second gas diffusion layer 13 is 0.4 mm.

[0119] The second frame 17 is molded in a molding machine at a molding pressure of 10 kg / cm². 2The hot-pressing temperature is 100℃, and the hot-pressing time is 2 minutes. The thickness of the first hot melt adhesive and the second hot melt adhesive is 20 μm. The overlap length between the first hot melt adhesive and the proton exchange membrane layer 11 is 2.9 mm, and the peel strength between the first hot melt adhesive and the proton exchange membrane layer 11 is 6 N / cm. The overlap length between the second hot melt adhesive and the proton exchange membrane layer 11 is 4.9 mm, and the peel strength between the first hot melt adhesive and the proton exchange membrane layer 11 is 5 N / cm. The overlap length between the first hot melt adhesive and the second hot melt adhesive is 1.3 mm, and the peel strength between the first hot melt adhesive and the second hot melt adhesive is 7 N / cm. At the same time, the second hot melt adhesive overflows from the end of the second frame 17 away from the proton exchange membrane layer 11 and adheres to the upper surface of the first frame 15. The overlap length between the overflowing second hot melt adhesive and the first frame 15 is 0.4 mm, thus preparing the membrane electrode 10.

[0120] Example 4

[0121] Example 4 is basically the same as Example 1, except that the glass transition temperature of the first hot melt adhesive and / or the second hot melt adhesive is 60°C.

[0122] Example 5

[0123] Example 5 is basically the same as Example 1, the main difference being that the materials of the first hot melt adhesive and the second hot melt adhesive are both proton-loving membrane polymers, that is, the same material is used.

[0124] Example 6

[0125] Example 6 is basically the same as Example 1, except that the thickness of the first hot melt adhesive and the second hot melt adhesive is 100 μm.

[0126] Example 7

[0127] Example 7 is basically the same as Example 1, the main difference being that in Example 7, the overlap length between the first frame 15 and the proton membrane layer 11 is 4 mm, and the overlap length between the first hot melt adhesive and the proton membrane layer 11 is 4.5 mm.

[0128] Example 8

[0129] Example 8 is basically the same as Example 1, the main difference being that in Example 8, the overlap length between the second frame and the proton membrane layer 11 is 6 mm, and the overlap length between the second hot melt adhesive and the proton membrane layer 11 is 6.5 mm.

[0130] Example 9

[0131] Example 9 is basically the same as Example 1, the main difference being that in Example 9, the peel strength between the first hot melt adhesive and the first surface is 3 N / cm hot melt adhesive.

[0132] Example 10

[0133] Example 10 is basically the same as Example 1, the main difference being that the overlap length between the first hot melt adhesive and the second hot melt adhesive in Example 10 is 0.5 mm.

[0134] Example 11

[0135] Example 11 is basically the same as Example 1, the main difference being that the overlap length between the first hot melt adhesive and the second hot melt adhesive in Example 11 is 2 mm.

[0136] Example 12

[0137] Example 12 is basically the same as Example 1, the main difference being that the peel strength between the first hot melt adhesive and the second hot melt adhesive in Example 12 is 3 N / cm.

[0138] Example 13

[0139] Example 13 is basically the same as Example 1, except that the gap between the first frame 15 and the first gas diffusion layer 12 is 0.1 mm and the gap between the second frame 17 and the second gas diffusion layer 13 is 0.1 mm.

[0140] Example 14

[0141] Example 14 is basically the same as Example 1, except that the gap between the first frame 15 and the first gas diffusion layer 12 is 1mm and the gap between the second frame 17 and the second gas diffusion layer 13 is 1mm.

[0142] Example 15

[0143] Example 15 is basically the same as Example 1, the main difference being that in Example 15, no second hot melt adhesive overflows from the end of the second frame 17 away from the proton membrane layer 11.

[0144] Example 16

[0145] Example 16 is basically the same as Example 1, except that the gap between the first frame 15 and the first gas diffusion layer 12 is 0mm and the gap between the second frame 17 and the second gas diffusion layer 13 is 0mm in Example 16.

[0146] Comparative Example 1

[0147] Comparative Example 1 is basically the same as Example 1, except that the thickness of the first hot melt adhesive and the second hot melt adhesive is 5 μm.

[0148] Comparative Example 2

[0149] Comparative Example 2 is basically the same as Example 1, except that the overlap length between the first frame 15 and the proton membrane layer 11 in Comparative Example 2 is 1 mm, and the overlap length between the first hot melt adhesive and the proton membrane layer 11 is 1.3 mm.

[0150] Comparative Example 3

[0151] Comparative Example 3 is basically the same as Example 1, except that the overlap length between the second frame and the proton membrane layer 11 in Comparative Example 3 is 2 mm, and the overlap length between the second hot melt adhesive and the proton membrane layer 11 is 2.3 mm.

[0152] The membrane electrode single-frame sealed structure obtained in the above embodiments is prepared with an active area of ​​25 cm². 2 The membrane electrode 10 was characterized and tested; a 15 μm GORE proton exchange membrane was selected as the proton exchange membrane, HISPEC 13100 was selected as the catalyst, and the gas diffusion layer was selected from the same manufacturer with the same substrate layer and microporous layer, only the thickness of the gas diffusion layer was different; the proton membrane layer was prepared as follows: the catalyst, isopropanol, deionized water and perfluorosulfonic acid polymer solution were mixed to prepare a catalyst slurry, which was then coated on the proton exchange membrane, wherein the cathode platinum loading was 0.3 mg / cm³. 2 The platinum loading at the anode is 0.1 mg / cm³. 2 .

[0153] The testing method or standard is as follows:

[0154] 1) Air tightness durability test: The frame is clamped in the single cell test fixture, the anode outlet, cathode inlet and coolant inlet and outlet of the fuel cell stack are sealed, a flow meter is connected to the cathode outlet, nitrogen gas is introduced from the anode inlet, the pressure is adjusted to 100 kPa, the flow meter reading is read, and the time when the leakage is greater than 1 mL / min is recorded. The air tightness durability time obtained by the test is shown in Table 1.

[0155] 2) Power density test: The assembled fuel cell stack with 6 membrane electrode assemblies 10, using graphite bipolar plates, was subjected to polarization curve testing. The cell inlet temperature was 80℃, the maximum operating temperature was 100℃, the cathode humidity was 60%, the anode humidity was 100%, the cathode / anode stoichiometric ratio was 1.8 / 1.5, and the test pressure was 100kPa. The volumetric power density test results of the fuel cell stack are shown in Table 1.

[0156] 3) High and Low Temperature Cycling Test: The membrane electrode was flattened using a single-cell test fixture for high and low temperature cycling tests. The single high and low temperature cycling test procedure was as follows: -30℃ (30 min); -30℃~95℃ (40 min); 95℃ (30 min); 95℃~-30℃ (40 min). Every 100 cycles, an airtightness test was performed, following the airtightness durability test method, with the pressure adjusted to 50 kPa. The number of cycles corresponding to a leakage rate greater than 1 mL / min was subtracted from 100 cycles, and this number was recorded as the high and low temperature cycle count. The number of high and low temperature cycles obtained from the tests is shown in Table 1.

[0157] Table 1

[0158]

[0159]

[0160] As shown in Table 1, the membrane electrodes 10 prepared in Examples 1 to 3 have a gas tightness durability time of >60 min and a high and low temperature cycle count of >1000, indicating that the membrane electrodes 10 in Examples 1 to 3 have excellent durability; at the same time, their stack power density is high.

[0161] Compared with Example 1, the glass transition temperature of the first hot melt adhesive and the second hot melt adhesive in Example 4 is 60°C. This glass transition temperature is in the middle of the operating temperature range of the membrane electrode. Therefore, the first hot melt adhesive and the second hot melt adhesive will undergo a phase transition. The test results show that the number of high and low temperature cycles is less, which makes the durability of the membrane electrode slightly worse.

[0162] Compared with Example 1, the first and second hot melt adhesives in Example 5 are made of the same materials, both using edge-adhesive adhesives. The test results show that the high and low temperature cycling resistance is slightly worse, which affects the airtightness of the interface between the hot melt adhesive and the proton exchange membrane layer.

[0163] Through Examples 1, 1 Comparative Example, and 6, it can be found that the hot melt adhesive layer in 1 is thin, which makes its airtightness durability time <60min, and the number of high-temperature cycles <500, making the airtightness of the membrane electrode unqualified; the hot melt adhesive layer in 6 is thicker, which can ensure the airtightness durability of the membrane electrode, but the power density of the stack is slightly lower.

[0164] Through Examples 1, 7, 8, Comparative Examples 2 and 3, it can be found that the overlap length between the frame and the proton membrane layer is small in Comparative Examples 2 and 3, which results in poor durability of the membrane electrode in Comparative Example 2; in Examples 7 and 8, the overlap length between the frame and the proton membrane layer is large, which results in a smaller active area of ​​the membrane electrode, which results in a slightly lower power density of the stack.

[0165] In Example 9, the peel strength between the first hot melt adhesive and the first surface is slightly low. Under varying temperature and humidity conditions, the proton exchange membrane will generate stress, which will slightly reduce the bonding force between the proton exchange membrane layer and the frame, resulting in slightly poorer gas tightness and durability of the membrane electrode.

[0166] Through Examples 1, 10, and 11, it can be found that when the embedding length of the first hot melt adhesive and the second hot melt adhesive is slightly smaller, the number of high and low temperature cycles is smaller, resulting in slightly poorer durability of the membrane electrode. In Example 11, the embedding length of the first hot melt adhesive and the second hot melt adhesive is slightly larger, resulting in slightly smaller active area of ​​the membrane electrode and slightly lower power density of the electrode stack.

[0167] In Example 12, the peel strength of the first sealing part and the first sealing layer is slightly small, which makes the airtightness of the first sealing part and the first sealing layer slightly poor, and thus the airtightness of the membrane electrode is slightly poor.

[0168] Through Examples 1, 13, 14, and 16, it can be observed that in Example 13, the gap between the first frame and the first gas diffusion layer is slightly smaller, and the gap between the second frame 17 and the second gas diffusion layer 13 is also slightly smaller. These gaps are slightly smaller than the membrane electrode assembly deviation, which may cause the gas diffusion layer to adhere to the frame, thus forming an air triangle in the frame and proton membrane region, slightly affecting the chemical reaction and resulting in a slightly lower stack power density. In Example 16, there is no gap between the first frame and the first gas diffusion layer, and the stack power density of Example 16 is slightly lower than that of Example 14. In Example 14, the gap between the first frame and the first gas diffusion layer is slightly larger, resulting in a slightly smaller active area of ​​the membrane electrode and consequently a slightly lower stack power density.

[0169] In Example 15, no second hot melt adhesive overflows from the end of the second frame 17 away from the proton membrane layer 11. The hot melt adhesive gas impact can easily cause the airtightness of the first and second frames to fail, resulting in slightly lower airtightness durability of the membrane electrode 10.

[0170] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0171] The embodiments described above are merely illustrative of several implementation methods of this application, intended to facilitate a detailed understanding of the technical solutions of this application, but should not be construed as limiting the scope of protection of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the scope of protection of this application. It should be understood that technical solutions obtained by those skilled in the art based on the technical solutions provided in this application through logical analysis, reasoning, or limited experimentation are all within the scope of protection of the appended claims. Therefore, the scope of protection of this patent application should be determined by the content of the appended claims, and the specification can be used to interpret the content of the claims.

Claims

1. A membrane electrode, characterized in that, It includes a proton exchange membrane layer, a first gas diffusion layer, a second gas diffusion layer, a first sealing layer, a second sealing layer, a first frame, and a second frame; The proton exchange membrane layer includes a first surface and a second surface disposed opposite to each other; The first gas diffusion layer is disposed on the first surface, and the second gas diffusion layer is disposed on the second surface; A first sealing layer is disposed on the first surface and connected to the first gas diffusion layer; and the first sealing layer extends out of the first surface in a direction away from the first gas diffusion layer; wherein the thickness of the first sealing layer is ≥10μm, and the overlap length between the first sealing layer and the first surface is ≥2 mm. A first frame is disposed on the side of the first sealing layer opposite to the first surface to provide support for the first sealing layer; The second sealing layer includes a first sealing portion, a second sealing portion, and an intermediate portion. The first sealing portion is embedded in one end of the first sealing layer away from the first gas diffusion layer. The second sealing portion is disposed on the second surface and is connected to the second gas diffusion layer. The end of the second sealing portion away from the second gas diffusion layer extends obliquely towards the first sealing portion to form the intermediate portion. The thickness of the second sealing layer is ≥10μm, and the overlap length between the second sealing layer and the second surface is ≥3mm. A second frame is disposed on the side of the second sealing layer opposite to the second surface, and is used to provide support for the second sealing layer; the shape of the second frame is adapted to the shape of the second sealing layer; A gap is left between the end face of the first frame near the first gas diffusion layer and the first gas diffusion layer, and the gap is filled by the first sealing layer; The second frame includes a first support portion, a second support portion, and a middle support portion. The first support portion is disposed on the side of the first sealing portion away from the first sealing layer. The second support portion is disposed on the side of the second sealing portion away from the second surface. A gap is left between the end face of the second support portion near the second gas diffusion layer and the second gas diffusion layer. The gap is filled by the second sealing portion. The end of the second support portion away from the second gas diffusion layer extends obliquely towards the first support portion to form a middle support portion. The middle support portion is disposed on the side of the middle portion away from the proton membrane layer.

2. The membrane electrode according to claim 1, characterized in that, The first sealing layer is formed by curing a first hot melt adhesive, the glass transition temperature of which is 80°C to 100°C. The second sealing layer is formed by curing a second hot melt adhesive; the glass transition temperature of the second hot melt adhesive is 80℃~100℃.

3. The membrane electrode according to claim 2, characterized in that, The membrane electrode has one or more of the following characteristics: (1) The material of the first hot melt adhesive forming the first sealing layer is a proton-loving membrane polymer; (2) The material of the second hot melt adhesive forming the second sealing layer is a first border-affinity polymer and / or a second border-affinity polymer; (3) The thickness of the first sealing layer is 10μm~50μm; (4) The thickness of the second sealing layer is 10μm~50μm.

4. The membrane electrode according to claim 1, characterized in that, The overlap length between the first sealing layer and the first surface is 2mm~4mm, and the peel strength between the first sealing layer and the first surface is ≥5N / cm; The overlap length between the second sealing layer and the second surface is 3mm~6mm, and the peel strength between the second sealing layer and the second surface is ≥5N / cm; The length of the first sealing part embedded in the first sealing layer is 1mm to 1.6mm, and the peel strength between the first sealing part and the first sealing layer is ≥7N / cm.

5. The membrane electrode according to claim 1, characterized in that, The gap length between the end face of the first frame near the first gas diffusion layer and the first gas diffusion layer is 0.3mm~0.5mm; the gap length between the end face of the second support near the second gas diffusion layer and the second gas diffusion layer is 0.3mm~0.5mm; the first sealing part overflows from the end of the first support part away from the proton membrane layer, and the overflow length of the first sealing part is 0.3mm~0.5mm.

6. The membrane electrode according to claim 1, characterized in that, The proton exchange membrane layer includes a proton exchange membrane and a catalyst layer disposed on two opposite surfaces of the proton exchange membrane. The outer dimensions of the catalyst layer are 0 mm to 2.7 mm smaller than the outer dimensions of the proton exchange membrane.

7. The membrane electrode according to claim 1, characterized in that, The membrane electrode has one or more of the following characteristics: (1) The thickness of the proton membrane is 20 μm to 50 μm; (2) The thickness of the first gas diffusion layer and / or the second gas diffusion layer is 150 μm ~ 300 μm; (3) The thickness of the first border and / or the second border is 12.5μm~200μm; (4) The material of the first frame and / or the second frame includes one or more of polyethylene terephthalate, polyimide, polyethylene naphthalate, polyphenylene sulfide and polyether ether ketone.

8. The membrane electrode according to any one of claims 1 to 7, characterized in that, The membrane electrode further includes a first electrode stack sealing strip and a second electrode stack sealing strip, which are respectively disposed on two opposite surfaces of the first frame and disposed at the end of the first frame away from the first gas diffusion layer.

9. The membrane electrode according to claim 8, characterized in that, The materials of the first and second fuel cell stack sealing strips are independently selected from one or more of silicone rubber, EPDM rubber, polyolefin rubber, fluororubber, polyurethane rubber and polyetheretherketone rubber.

10. A method for preparing a membrane electrode according to any one of claims 1 to 9, characterized in that, Includes the following steps: The first gas diffusion layer and the second gas diffusion layer are respectively placed on two opposite surfaces of the proton membrane layer; The first frame coated with a first hot melt adhesive and the second frame coated with a second hot melt adhesive are placed and hot-pressed together, and the first hot melt adhesive and / or the second hot melt adhesive are cured to form the first sealing layer and the second sealing layer, thereby preparing the membrane electrode.

11. The method for preparing a membrane electrode according to claim 10, characterized in that, The hot pressing process parameters include: hot pressing pressure of 1 kg / cm². 2 ~20kg / cm 2 The hot pressing temperature is 80℃~150℃.

12. A proton exchange membrane fuel cell, characterized in that, Includes the membrane electrode as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Fuel cell membrane electrode, preparation method thereof and fuel cell

    CN114420944A

  • membrane electrode assembly and fuel cell stack

    DE102017101954A1